Insights Into the Different Effects of Food on Intestinal Secretion Using Magnetic Resonance Imaging. Issue 8 (30th March 2018) - Wilkinson‐Smith, Victoria C.; Major, Giles; Ashleigh, Lucy; Murray, Kathryn; Hoad, Caroline L.; Marciani, Luca; Gowland, Penny A.; Spiller, Robin C.; ,
Abstract: Background: Plant foods may stimulate intestinal secretion through chemicals designed to deter herbivores, including lactucins in lettuce and rhein in rhubarb. This may increase ileostomy output and induce diarrhoea in people with intact bowels. Objective: We aimed to determine the effect of food on intestinal water content using Magnetic Resonance Imaging (MRI). Design: A three period crossover trial of isocaloric meals in adults without bowel disorders. Meals: 2 slices white bread with 10 g butter; 300 g rhubarb with 60 mL lactose free cream; 300 g lettuce with 30 mL mayonnaise. Primary outcome: Area under curve (AUC) small bowel water content (SBWC) using MRI. Secondary outcomes: ascending colon water content; T1 relaxation time of ascending colon (T1AC); gastric volume; visual analogue scales of bloating and satiety (0–100). MRI analysts were blinded. Scanned fasting and hourly to 180 min postprandial. Symptoms scored half‐hourly. Results: 9 female and 6 male subjects completed the study. AUC SBWC fell after bread but rose after lettuce and even more after rhubarb, difference from baseline being (Bread AUC −5662 (1209) ml.min vs Lettuce 3194 (1574) ml.min and Rhubarb 10586 (1629) ml.min ( P < 0.01). Rhubarb induced a rise in T1AC but differences at 3 hours were not significant ( P = 0.06). Gastric volume at T = 0 significantly was higher for both lettuce and rhubarb (571 ± 92 and 558 ± 89 mls) respectively compared to bread (314 ± 108 mls) ( p < 0.0001). Symptom scores were higher for lettuce > rhubarb > bread. Conclusion: Lettuce and rhubarb meals increased intestinal water content, demonstrating how different foods can alter ileal flow and stool consistency.